Pengalaman Mahasiswa pada Sistem Pembelajaran Daring (E-Learning) di Masa Pandemi Covid-19 (Studi Kasus Mahasiswa Jurusan Teknologi Informasi Politeknik Negeri Malang) - Nurma Afi Nirmala; Diah Priharsari; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The purpose of this study was to express students' opinions from the experiences they felt due to the impact of physical distancing that required the closure of schools, universities, and training centers, as well as the obstacles they experienced during the implementation of online learning to prevent the spread of the Covid-19 pandemic. The purpose of this study was to express students' opinions from the experiences they felt due to the impact of physical distancing that required the closure of schools, universities, and training centers, as well as the obstacles they experienced during the implementation of online learning to prevent the spread of the Covid-19 pandemic. Therefore, data collection of students' experience of online learning using qualitative descriptive methods that are explorative through semi-structural interviews in depth involving 10 students of the Information Technology Department of the Malang State Polytechnic. The number of participants is obtained from the results of saturation data. The results of semi-structural interview data collection are then made into verbatim transcripts and analyzed with thematic coding, and divided into main themes, secondary themes, and code. It is concluded that students have an unlikable experience of three aspects of information system problems related to technology and information linking, organizations, and individuals. Issues such as students feeling dissatisfied due to lack of synchronous educational activities, lack of interaction and communication, failure to understand the material given and dissatisfied with the way of teaching from some lecturers became an unlikable experience of online learning activities. This research can be information and suggestions in improving online learning in the future.